On one model approach to assessment of state for the stock of walleye pollock Theragra chalcogramma in the northern Okhotsk Sea - Oleg I. Ilyin; Aleksander. I. Varkentin; Anatoly. V. Smirnov (Известия ТИНРО)
One possible approach to the stock assessment for marine commercial fish species is considered by the example of the Okhotsk Sea pollock. The method is based on cohort modeling. Unknown parameters of the model are selected by solution of the filtration and identification problem.